KONSEP “MANUSIA EKONOMI” DALAM PEMBANGUNAN EKONOMI DAN PENDIDIKAN - Riswan Jaenudin (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2014)
The essence of economic problems is the use of scarce resources to satisfy unlimitedhuman needs. Scarcity is inevitable and scarcity is central to economic problems. The infinitehuman need is supposedly derived from the philosophy of "hedonism" which has succeeded increating the concept of "economic man" and the monistic view can not explain the nature ofman as a whole because the monistic view is more more individualistic and materialistic. Theconcept of human economics can work in harmony or support a sustainable developmentapproach that is ecologically oriented when people realize that they are not just economicbeings but also as social beings, cultured beings, religious beings, must be balanced,harmonious and harmonious between economic activity and ecology . Furthermore, theconcept of an alternative to saving learners from human economic behavior is through tieredand continuous schooling, and out-of-school education includes education in families, studygroups, courses and other similar education tailored to the level of development of learners.